Bad dog, Marley! - Grogan, John, 1957-; Cowdrey, Richard (New York, N.Y. : HarperCollinsPublishers, 2007)
Marley, a rambunctious puppy, makes himself at home while causing lots of trouble but then proves in a very dramatic way that he is a valuable member of the household.
Keywords: Dogs -- Juvenile fiction